2018
DOI: 10.1039/c7dt04554a
|View full text |Cite
|
Sign up to set email alerts
|

Spectroelectrochemical studies of a ruthenium complex containing the pH sensitive 4,4′-dihydroxy-2,2′-bipyridine ligand

Abstract: Attaining high oxidation states at the metal center of transition metal complexes is a key design principle for many catalytic processes. One way to support high oxidation state chemistry is to utilize ligands that are electron-donating in nature. Understanding the structural and electronic changes of metal complexes as higher oxidation states are reached is critical towards designing more robust catalysts that are able to turn over at high rates without decomposing. To this end, we report herein the changes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 84 publications
2
3
0
Order By: Relevance
“…have used the value of 1210 mV vs Fc +/0 for HMB as a reference for their redox ladder, we have chosen [Ru­(bpy-(OMe) 2 ) 3 ] 2+ with a reversible couple at a less positive potential of 557 mV vs Fc +/0 as our reference. We believe that using reference couples with less anodic potentials provides better accuracy for determining true E °′ due to the stability of oxidized species as demonstrated for [Ru­(bpy-(OMe) 2 ) 3 ] 3+ using cyclic voltammetry and UV–vis spectroelectrochemistry . The redox scale measured by PR is consistent with the potential of BP determined by Guldi et al using AC voltammetry .…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…have used the value of 1210 mV vs Fc +/0 for HMB as a reference for their redox ladder, we have chosen [Ru­(bpy-(OMe) 2 ) 3 ] 2+ with a reversible couple at a less positive potential of 557 mV vs Fc +/0 as our reference. We believe that using reference couples with less anodic potentials provides better accuracy for determining true E °′ due to the stability of oxidized species as demonstrated for [Ru­(bpy-(OMe) 2 ) 3 ] 3+ using cyclic voltammetry and UV–vis spectroelectrochemistry . The redox scale measured by PR is consistent with the potential of BP determined by Guldi et al using AC voltammetry .…”
Section: Resultssupporting
confidence: 80%
“…We believe that using reference couples with less anodic potentials provides better accuracy for determining true E°′ due to the stability of oxidized species as demonstrated for [Ru(bpy-(OMe) 2 ) 3 ] 3+ using cyclic voltammetry 28 and UV−vis spectroelectrochemistry. 42 The redox scale measured by PR is consistent with the potential of BP determined by Guldi et al using AC voltammetry. 13 Regardless of the choice of a reference potential, the comparison of data in Table 2 to values determined photochemically and those obtained by AC voltammetry demonstrates the applicability of the PR equilibrium technique for determining the potentials of biphenyl and benzene derivatives.…”
Section: The Journal Ofsupporting
confidence: 85%
“…Theoretical calculations: assignment of the lowest excited state of the complexes Theoretical calculations have been successfully used to reveal the photophysics of Ru(II) polypyridyl complexes. [55][56][57][58][59] We carried out DFT/TD-DFT calculations for the studied complexes in ethanol (Table 1). We found that for Ru1 and Ru2 the lowest singlet (S 1 ) and triplet states (T 1 ) are the MLCT states.…”
Section: Papermentioning
confidence: 99%
“…In work similar to the original Meyer paper, we reported a system that utilized a Ru II diimine complex bearing a hydroxylated bipyridine ligand and MQ + . In this system, we explored the thermodynamic landscape of reactions. We discovered that despite the favorability of a concerted PCET reaction from the excited-state potential energy surface, outer sphere electron transfer was observed. We speculated that because of a combination of electrostatic repulsion from the same charge species and a small driving force for proton transfer, and therefore also weak hydrogen bonding, the otherwise favorable concerted excited-state PCET (PCET*) reaction was not observed.…”
Section: Introductionmentioning
confidence: 99%